RESPON PERTUMBUHAN, HASIL DAN MUTU BAWANG MERAH (Allium ascalonicum L.) VARIETAS TAJUK AKIBAT PERLAKUAN KONSENTRASI ECO ENZYM PISANG DAN PUPUK ORGANIK MASSA DAUN - Bakir Bakir; Siti Asmaniyah Mardiyani; Anis Sholihah (AGRONISMA, 2022)
The cause of onion products in Indonesia since 2013 ago it causes the application of chemical fertilizer as long as over the time. Thus, the onion was dropped out because it has occasioned soil sickness and soil fatigue. It has been the cause of harm matter that was not equal and less the organic fertilizer. The fertilizer has been a positive impact on the plant. However, there was the other fertilizer that was used by farmers. It was an eco-enzyme. It is made from banana shell waste and other vegetables. This research has done in Green House that on October until December 2021. The location was in Jalan MT. Haryono, Dinoyo, Lowokwaru, Malang City. Which were Â± 505 mdpl the temperature on 25c-30c and the rainfall was 1750mm/year.This research used the RAK method. Which were used 3 repetition factorials. There were many factors in each factor. First, the application concertation of the eco-enzyme was E0=0%, E1=1,5%, E2=3%. The second was the allotment of organic fertilizer based on leaf mass. Wich was P0= 0 ton-1 ha, P1= 5 ton-1 ha, P2= 10 ton-1 ha dan P3= 15 ton-1 ha. The parameter of this research was plant height, number of leaves, number of tillers, chlorophyll content of tubers planted, big fresh plant total, dry tuber weight total dissolved solids analysis, and vitamin c content.The result of this research was first, the impact of concentration eco enzyme and dose of organic fertilizer of leaf mass. It provided the real of interaction to onion quality (allium ascolonicum L) in contains chlorophyll was on 5 HST. Which (46.28 Âµg/cm2) was done by concentration eco enzyme 0 ml/l and those of fertilizer 10 ton. The second, the impact of concentration eco enzyme that given the real impact of plant quality. It generated vitamin c at 49.87 mg ad 38.13 mg. The third, the best dose impact of organic fertilizer leaf mass was 5ton ha (P1) and 10ton ha (P2) which produced the consistent value of the plant height (41.12) and a total of the leaf (38.11 sheets)